PENGARUH VARIAN ANGGARAN, UKURAN PEMERINTAH DAERAH, DAN KAPASITAS FISKAL TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH - Afifah, Safira Izzatul; Adnan, Adnan (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2022)
This study aims to examine the effect of budget variance, local government size and fiscal capacity on the financial performance of district/city governments in Aceh in 2018-2020 based on efficiency ratios and effectiveness ratios. The data used is secondary data from local government financial reports that have been audited by BPK RI. The data analysis method used is Spearman's Rho Correlation, Multiple Linear Regression Test and Coefficient of Determination Test. This study uses two regression models. The first model of the dependent variable of financial performance is measured using the efficiency ratio and in the second model the dependent variable of financial performance is measured using the effectiveness ratio. The results showed that the budget variance and fiscal capacity partially had no effect on the financial performance of local governments based on efficiency ratios, while the variable size of local government has a negative and significant effect on the financial performance of local governments based on efficiency ratios. In the second model that uses the effectiveness ratio, budget variance and fiscal capacity have a negative and significant effect on local government financial performance, while the variable size of local government has no significant effect on the financial performance of local governments based on the effectiveness ratio. The result of the Coefficient of Determination analysis is 0.023, which means that the budget variance, size of local government and fiscal capacity can explain 2.3% of local government financial performance based on efficiency ratios. While in model 2, the coefficient of determination is 0.246, which means that the budget variance, the size of the local government and the fiscal capacity can explain 24.6% of the financial performance of the local government based on the effectiveness ratio.